(untitled) (Research, Society and Development, 2021)
The article reports experiences acquired during activities carried out in an Online training with teachers of Basic Education in the municipality of Breves, in the Marajó archipelago (State of Pará, Brazil). Such extension action took place during the month of March in 2021. The methodological path took place through two virtual environments, through the Google Meet and Google Classroom platform. This case study consisted of bibliographic research and action research. The training aimed to reflect, debate and propose innovative pedagogical practices aimed at anti-racist education in Marajoara territory. Thus, the participants had the opportunity not only to understand pedagogical concepts and practices offered in training, but also to seek to build a more human and inclusive educational culture through virtual learning environments.